Pro MySQL - Kruckenberg, Michael (Apress, 2012)
Data, in all varieties, continues to be the cornerstone from which modern organizations and businesses derive their information capital. Whether putting items in an online shopping cart for checkout or tracking terabytes of purchase history to find shopping trends, having a database to store and retrieve data has become a necessity. From the individual to the small nonprofit organization, the small business to the large corporation, retrieving stored information at the right time and in the right format is helping people make more informed business decisions. The demand for larger amounts of data, stored in more user-friendly formats and using faster database tools, continues to grow.3